2016
DOI: 10.1021/acs.jpcc.6b06545
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Confinement Effects in Organic Lead Tribromide Perovskite Nanoparticles

Abstract: The optical and electronic properties of nanoparticles/nanocrystals (NC) of methylammonium lead tribromide perovskite (MAPbBr 3 ) have been studied in detail. We observe the effect of quantum confinement in particles of an average diameter of ∼6 nm and smaller, in the form of an increase in excitonic nature with decrease in particle size. The differences in the photophysical properties in bulk and NC forms of MAPbBr 3 are clearly observed in the temperature dependent measurements, and provide insight into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…reported the synthesis of stable perovskite nanocrystals (PNC) having good emission characteristics, and their application in electroluminescent devices . Following this report, several studies done by various groups suggest that hybrid perovskites in nanocrystal form are suitable for most of the above‐mentioned applications . In this context, very recently, we have demonstrated the excellent energy migration properties of these materials .…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…reported the synthesis of stable perovskite nanocrystals (PNC) having good emission characteristics, and their application in electroluminescent devices . Following this report, several studies done by various groups suggest that hybrid perovskites in nanocrystal form are suitable for most of the above‐mentioned applications . In this context, very recently, we have demonstrated the excellent energy migration properties of these materials .…”
Section: Introductionmentioning
confidence: 74%
“…In order to use a material as light‐harvesting antenna, it has to display two capabilities, that is, excellent light absorption and efficient energy transfer to the acceptors. In this context, luminescent PNCs are potential candidates as they exhibit intense light absorption and good fluorescence quantum yield due to the quantum confinement effect . Moreover, they possess a high surface area, which helps them interact effectively with suitable acceptor dyes through electrostatic forces.…”
Section: Introductionmentioning
confidence: 99%
“…A more accurate method of determining the perovskite bandgap energies using the Elliot theory was applied by Kumawat et al . and other researchers; using this method, bandgap energies were found to vary from 2.42 (in case of MAPbBr 3 ) to 3.16 eV (in case of MAPbCl 3 ) as the concentration of the Cl ion ( x ) was varied from 0 to 1 in MAPb(Br 1− x Cl x ) 3 …”
Section: Optical Propertiesmentioning
confidence: 99%
“…As n increases,t he energies of the exciton lines converge and at the band edge the absorption coefficient becomes large and becomes large and finite instead of being zero below the excitonic peak wavelength. Am ore accurate method of determining the perovskite bandgap energies using the Elliot theory [75,76] was applied by Kumawat et al [32] and other researchers; [77,78] using this method, bandgap energies were found to vary from 2.42 (in case of MAPbBr 3 )t o3 .16eV( in case of MAPbCl 3 )a st he concentration of the Cl ion (x)w as varied from 0t o1in MAPb(Br 1Àx Cl x ) 3 . [32]…”
Section: Tuning Optical Bandgap In Mixed-halide Perovskitesmentioning
confidence: 99%
“…[1][2][3][4][5] The fascinating properties of lead halide perovskites such as broad absorption, narrow emission with near unity quantum yield, easier carrier extraction, and high photovoltaic efficiency proffered them as active materials for photovoltaic and light-emitting applications. [3,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Till today, lead halide perovskite is one of the materials which has shown the highest efficiency for light-emitting diodes (LEDs) and photovoltaic applications. [1,6,[21][22][23][24][25][26] These interesting properties of perovskites are mainly due to their peculiar crystal structures.…”
mentioning
confidence: 99%